Application of Mahalanobis-Taguchi system in descending case of methadone flexi dispensing (MFlex) program - S. K. M., Saad; S. N. A. M., Zaini; M. Y., Abu (Penerbit UMP, 2021)
Patient under methadone flexi dispensing (MFlex) program is subjected to do methadone dosage trends for descending case since no parameters were employed to identify the patient who has potential rate of recovery. Consequently, the existing system does not have a stable ecosystem towards classification and optimization due to inaccurate measurement methods and lack of justification of significant parameters which will influence the accuracy of diagnosis. The objective is to apply Mahalanobis-Taguchi system (MTS) in the MFlex program as it has never been done in the previous studies. The data is collected at Bandar Pekan clinic with 16 parameters. Two types of MTS methods are used like RT-Method and T-Method for classification and optimization respectively. In classification of descending case, the average Mahalanobis distance (MD) of healthy is 1.0000 and unhealthy is 11123.9730. In optimization of descending case, there are 9 parameters of positive degree of contribution. 6 unknown samples have been diagnosed using MTS with different number of positive and negative degree of contribution to achieve lower MD. Type 6 of 6 modifications has been selected as the best proposed solution. In conclusion, a pharmacist from Bandar Pekan clinic has confirmed that MTS is able to solve a problem in classification and optimization of MFlex program.